Carbon Allocation in Rhodococcus jostii RHA1 in Response to Disruption and Overexpression of nlpR Regulatory Gene, Based on 13C-labeling Analysis - Hernández, Martín A.; Gleixner, Gerd; Sachse, Dirk; Alvarez, Héctor M. (Frontiers in Microbiology, 2017)
NlpR is a pleiotropic regulator that positively controls genes associated with both nitrogen and lipid metabolism in the oleaginous bacterium Rhodococcus jostii RHA1. In this study, we investigated the effect of nlpR disruption and overexpression on the assimilation of 13C-labelled glucose as carbon source, during cultivation of cells under nitrogen-limiting and nitrogen-rich conditions, respectively. Label incorporation into the total lipid extract (TLE) fraction was about 30% lower in the mutant strain in comparison with the wild type strain (WT) under low-nitrogen conditions. Moreover, a higher 13C abundance ( 60%) into the extracellular polymeric substance (EPS) fraction was observed in the mutant strain. nlpR disruption also promoted a decrease in the label incorporation into several TLE-derivative fractions including NL (neutral lipids), GL (glycolipids), phospholipids (PL), triacylglycerols (TAG), diacylglycerols (DAG), and free fatty acids (FFA), with the DAG being the most affected. In contrast, the nlpR over-expression in RHA1 cells under nitrogen-rich conditions, produced an increase of the label incorporation into the TLE and its derivative NL and PL fractions, the last one being the highest 13C enriched. In addition, a higher 13C enrichment occurred in the TAG, DAG and FFA fractions after nlpR induction, with the FFA fraction being the most affected within the TLE. Isotopic-labelling experiments demonstrated that NlpR regulator is contributing in oleaginous phenotype of R. jostii RHA1 to the allocation of carbon into the different lipid fractions in response to nitrogen levels, increasing the rate of carbon flux into lipid metabolism.